2008
DOI: 10.1007/s00294-008-0203-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the rDNA-encoded mitochondrial protein Tar1p is stringently controlled and responds differentially to mitochondrial respiratory demand and dysfunction

Abstract: The novel yeast protein Tar1p is encoded on the anti-sense strand of the multi-copy nuclear 25S rRNA gene, localizes to mitochondria, and partially suppresses the mitochondrial RNA polymerase mutant, rpo41-R129D. However, the function of Tar1p in mitochondria and how its expression is regulated are currently unknown. Here we report that Tar1p is subject to glucose repression and is up-regulated during post-diauxic shift in glucose medium and in glycerol medium, conditions requiring elevated mitochondrial respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 39 publications
4
26
0
Order By: Relevance
“…Luciferase expression driven by the TAR1 5′ flanking regions was however 7 to 14-fold higher than controls indicating that their enhancer effect was more important in respiratory than in non-respiratory growth. This is consistent with the reported induced expression of a chromosomal TAR1 -lacZ fusion in glycerol versus glucose medium [10]. Using western blot analyses, we found that the endogenous Tar1p protein was however less detectable in growing condition that requires respiration (lactate), than in glucose or galactose (Figure 5F), Thus, whereas reporter systems [10] (and this work) indicated an induction of TAR1 expression under respiratory conditions, our western analyses did not show a correlated increase in the amount of endogenous Tar1p.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Luciferase expression driven by the TAR1 5′ flanking regions was however 7 to 14-fold higher than controls indicating that their enhancer effect was more important in respiratory than in non-respiratory growth. This is consistent with the reported induced expression of a chromosomal TAR1 -lacZ fusion in glycerol versus glucose medium [10]. Using western blot analyses, we found that the endogenous Tar1p protein was however less detectable in growing condition that requires respiration (lactate), than in glucose or galactose (Figure 5F), Thus, whereas reporter systems [10] (and this work) indicated an induction of TAR1 expression under respiratory conditions, our western analyses did not show a correlated increase in the amount of endogenous Tar1p.…”
Section: Resultssupporting
confidence: 92%
“…Selection of nuclear rDNA fragments acting as genetic suppressors was independently described in a screen that used a mutant of the Rpo41p mitochondrial RNA polymerase [8]. In this case, while a moderate expression of TAR1 ORF was found to rescue the respiration-deficient phenotype of the rpo41 mutant [8], a high expression exacerbated the defects of the mutant [10]. Genetic interaction between the rDNA-nested TAR1 ORF and the RPO41 gene is thus unclear as is the selection of nuclear rDNA portions in genetic screens based on the rescue of respiration-deficient phenotypes in yeast.…”
Section: Introductionmentioning
confidence: 99%
“…Bonawitz et al (2008) proposed that Tar1p was induced under respiratory conditions to maintain oxidative phosphorylation capacity. Thus, Al-induced upregulation of leaf Tar1p (TDF #134-1; Table 1) might provide an adaptive strategy of plants to Al-toxicity by increasing the efficiency of oxidative phosphorylation.…”
Section: Nucleic Acid Metabolism Genesmentioning
confidence: 99%
“…The rDNA of many organisms, including yeast and humans, encodes RNAPII-expressed transcripts that must be expressed at certain stages without causing general instability (Coelho et al, 2002; Kobayashi and Ganley, 2005; McStay and Grummt, 2008). In yeast, the TAR1 gene, encoded in the anti-sense direction of the 35S gene, is of particular interest because it is specifically expressed upon nutrient depletion (Bonawitz et al, 2008; Galopier and Hermann-Le Denmat, 2011), coincident with positional desilencing. Strikingly, nutrient-dependent regulation of TAR1 is lost when the gene is analyzed on a plasmid (Galopier and Hermann-Le Denmat, 2011), suggesting that rDNA structure contributes regulatory control.…”
Section: Discussionmentioning
confidence: 99%